2020
DOI: 10.21203/rs.2.19628/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of educational intervention based on precede proceed model on life quality in hypertensive patients

Abstract: Background: Hypertension is considered as one of the major risk factors for cardiovascular diseases killing over 9 million people worldwide each year . Methods: This experimental study was performed in 90 patient’s hypertension attending health centers affiliated to karaj University of Medical Sciences. The subjects were randomly assigned into two groups of intervention (n=45) and control (n=45). The data were collected through questionnaires. Educational intervention was designed based on PRECEDE-PROCEED mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This model pays attention to several factors that comprise the health status of individuals and clearly defines and interprets them (Moshki et al, 2017) and is founded in social/behavioural science, epidemiology, administration and education. The systematic use of this framework in a series of clinical trials confirmed the utility and predictive validity of the model as a planning tool and as a participatory model for creating successful community health promotion and other public health interventions (Green et al, 1975), such as educational intervention on life quality in hypertensive patients (Azar et al, 2020). Or community pharmacy for health needs assessment (Handyside et al, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 84%
“…This model pays attention to several factors that comprise the health status of individuals and clearly defines and interprets them (Moshki et al, 2017) and is founded in social/behavioural science, epidemiology, administration and education. The systematic use of this framework in a series of clinical trials confirmed the utility and predictive validity of the model as a planning tool and as a participatory model for creating successful community health promotion and other public health interventions (Green et al, 1975), such as educational intervention on life quality in hypertensive patients (Azar et al, 2020). Or community pharmacy for health needs assessment (Handyside et al, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 84%
“…Poor lifestyle choices, inappropriate self-management, and the increase of comorbidities such as hypertension persist despite several studies on diabetes education.This study aims to assess the impact of an educational intervention based on the PRECEDE model on diabetes patients' lifestyle, self-management, and hypertension. Furthermore, create a framework that predisposing factors (knowledge, attitude, and perceptions), reinforcing factors (influence of others, family, and peers), and enabling factors (availability of resources and skills) are considered as factors affecting behavior in educational diagnosis [18].…”
Section: Introductionmentioning
confidence: 99%